2020
DOI: 10.1182/blood.2019000794
|View full text |Cite
|
Sign up to set email alerts
|

Ldb1 is required for Lmo2 oncogene–induced thymocyte self-renewal and T-cell acute lymphoblastic leukemia

Abstract: Prolonged or enhanced expression of the proto-oncogene Lmo2 is associated with a severe form of T-cell acute lymphoblastic leukemia (T-ALL), designated early T-cell precursor ALL, which is characterized by the aberrant self-renewal and subsequent oncogenic transformation of immature thymocytes. It has been suggested that Lmo2 exerts these effects by functioning as component of a multi-subunit transcription complex that includes the ubiquitous adapter Ldb1 along with b-HLH and/or GATA family transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…HAMP has a strong correlation with immune and carcinoma. Studies concerned about LYL1 mainly focused on lymphoblastic leukemia which indicated LYL1 acted as a oncogene in acute lymphoblastic leukemia and induced the development and progression of acute lymphoblastic leukemia 65–69 and LYL1 has been demonstrated to regulate the early lymphoid differentiation of immature hematopoietic cells, 70 which suggested it is possible for the association between immune infiltration and LYL1 in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…HAMP has a strong correlation with immune and carcinoma. Studies concerned about LYL1 mainly focused on lymphoblastic leukemia which indicated LYL1 acted as a oncogene in acute lymphoblastic leukemia and induced the development and progression of acute lymphoblastic leukemia 65–69 and LYL1 has been demonstrated to regulate the early lymphoid differentiation of immature hematopoietic cells, 70 which suggested it is possible for the association between immune infiltration and LYL1 in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although data for cells in the same developmental stages with complete disruption of Ikaros ( Ikzf1 ) were not available, differentially expressed genes that responded to Ikaros ( Ikzf1 ) zinc finger 4 deletion were also added ( 85 ). Finally, we included data from studies of acute gain of function of factors at stages after they would normally have been shut down, including PU.1 ( Spi1 ) ( 48 ), and the transcription factor adaptor Lmo2 ( 86 88 ). In addition, supporting results came from studies introducing into pro-T cells acute antagonists of key transcription factors, including the natural E protein antagonist ID2 ( 89 ) or an artificially constructed dominant repressor form of PU.1 ( 90 ).…”
Section: Gene Regulatory Network Models As Explanations Of Developmen...mentioning
confidence: 99%
“…However, overexpression of Lmo2 or Lyl1 in thymocytes does not drive the T cell program. Instead, it causes T-cell lymphoma/leukemia, and when Lmo2 is involved, it causes increased expression of genes associated with progenitor fates ( 86 88 , 201 203 )( Figures 4B, C , top). Under these conditions, the Lmo2/Lyl1 protein complex directly activates Hhex , which upregulates Kit expression (encoding the growth factor receptor cKit) and promotes self-renewal ( 91 ) at the expense of T-lineage differentiation.…”
Section: Gene Regulatory Network Models For Early T Cell Development ...mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, some papers have reported the functions and roles of LDB1 in several tumors. For example, in the proto-oncogene LMO2-induced T-cell acute lymphoblastic leukemia, LMO2 along with LDB1, b-HLH and GATA formed a multi-subunit transcription complex, which was required for the oncogenic transformation of immature thymocytes ( 10 ). Another paper also confirmed that LDB1 enhanced the stability of direct and indirect oncoprotein partners in leukemia, such as LMO2 ( 11 ).…”
Section: Introductionmentioning
confidence: 99%